Facilitating Nursing Research: A professional mandate for Perioperative Nurses - Michael, Rene (Operating Room Nursing Association of Canada (ORNAC), 2007)
Health care and health care technology are becoming increasingly complex and expanding at an unprecedented pace. To thrive within this milieu, nursing as a profession must not only keep up with the pace but also set the pace for the future of health care. Nurses are constantly challenged to expand their 'comfort zone' by presenting creative approaches to health care, and developing new and innovative interventions that make a difference to the health status of patients and the community as a whole. As a consequence of this challenge, the question is raised: How do we as perioperative nurses expect to be competent technically, demonstrate independent judgement and skilled decisionmaking, and keep our knowledge base and practice current? The answer is through research.The ultimate importance of research is found in its definition. Research generates knowledge. Nursing research provides a specialised scientific base that empowers the profession to anticipate and meet these constantly shifting challenges, and maintain-our societal relevance. This in turn allows us to make better-informed decisions and validates existing practices built through tradition, intuition and personal experience. Research can examine tried and true practices and make them more efficient, less expensive, less complicated1 or debunk them!The introduction of evidence-based practice in Australia is perhaps the most powerful influence in promoting the utilisation of research in clinical practice and impacting on how nurses think about and use research. Evidence-based nursing is clinical activity that is based on the premise that the best available current scientific evidence should inform decisions about the delivery of care to patients. This means nurses adopt effective practices by questioning whether there is a scientific basis for the care that they deliver, in order to provide quality care for their patients and their families. However, to provide evidence-based practice nurses must participate in research including reading, understanding and applying the available research literature to promote positive patient outcomes1. In essence, we need to be scholars who know and use research principles in clinical practice.